MARKETING ON POLITICS AND PUBLIC LEADERSHIP - Purwanto Purwanto; Eddy Madiono Sutanto; Asmara Indahingwati (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2018)
This study examines the influence of political marketing and political will on public leadership and individual performance. The sample used is the people in Surabaya as many as 265 with a random sampling method. Amos 21 is used to test the indirect effect by using bootstrap test. The result of the research shows that political marketing and political will have a significant influence to the success of gaining public leadership, political marketing and marketing will have no significant effect on performance, and public leadership has a significant effect on performance. For the indirect influence, political marketing and political will on individual performance are mediated by public leadership.